Study of Ossification Centres Around the Elbow and Wrist of Adolescent Age Group 15-18 Years - Kishore Kumar.G; R.Jenifer Jacquiline (Indian Journal of Forensic Medicine & Toxicology, 2022)
Intoduction: Determination of age in both living and dead plays a pivotal role in medicolegal cases.There are various parameters to assess the age by physical characteristics, odontological developmentbut the most valuable method seems to be the osteological changes observed by radiological examinationie., the appearance and fusion of secondary ossification centres around respective joints The presentstudy was conducted on 131 subjects out of which 110 were males and 21 were females. The main aimof the study was to find the age of fusion of secondary ossification centres around elbow and wrist joint,to compare the distribution of fusion of ossification centres between males and femalesMethods: Firstly informed consent was taken. Preliminary details of each individual was noted thatincluded general examination, physical examination, dental examination followed by taking X-ray APview of elbow and wrist joint for radiological examination. The results were noted based on the degreeof fusion as No Union (O), Beginning union(B), Recent union(R), Complete union(C).Results: The present study showed among males, the fusion for each ossification centre around elbowjoint started by 15-16 years and was completed by 18-19 years whereas in females it started fusion by15-16 years but complete fusion occurred around 16-17 years itself . In wrist joint the fusion starts at16-17 years in males but only fusion of lower end of ulna is completed by 18-19 years, however bothlower end of radius and ulna are fused by 18-19 years in females.Conclusion: Based on the analysis of fusion of ossification centres it shows that both thecentres aroundelbow and wrist joint fuses earlier in females by 1-2 years than males.